Evaluation of Deconcentration Funds in the Regional Development Planning Agency (Bappeda) Central Java Province - Azzahra Salsabila Puspitasari; Alikha Novira (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Deconcentration funds are one form of the central government to hold an equitable government in each region using the State Revenue and Expenditure Budget (APBN). The implementation of this deconcentration fund is directly supervised by the governor as a representative of the central government which is included in vertical agencies. The research method used in this journal is the CSE-UCLA evaluation model with research approach used using a qualitative approach with documentation, interviews, and observation methods. Most of the data taken are from the results of documentation studies with data analysis techniques, namely data reduction, data presentation, and conclusion. In the use of deconcentration funds in the Central Java Province for the budget year 2021, which is Rp. 1,144,613,000, - (one billion one hundred forty-four million six hundred thirteen thousand rupiah) which among others is used for expenditure on operational goods, expenditure on non-operational goods, expenditure on supplies, service expenditure, and expenditure on domestic business trips. In its implementation, two obstacles occur. The first obstacle is the change in administrative requirements for disbursing deconcentration funds. The second obstacle occurred because of the COVID-19 pandemic, so there were several activities whose implementation was delayed until the situation could be said to be safe to carry out activities.